Perancangan Sistem SPPD Pada Balai Pengelola Kereta Api Ringan Sumatera Selatan (BPKARSS) - Septorio, M Luthfi; Purwani, Fenny; Ipandy, Ahkmad (MDP Student Conference, 2024)
Balai Pengelola Kereta Api Ringan Sumatera Selatan (BPKARSS) manages light trains in South Sumatra and routinely sends employees on business trips. Business trips outside the company aim to advance BPKARSS, with each employee requiring a Travel Order Letter (SPPD) as permission from superiors. The process of appointing delegates often experiences duplication and delays in report generation, causing delegates who are on a trip to be reassigned. This research focuses on designing the SPPD system to address these issues using prototype methods and UML Modelling. The research findings indicate that the SPPD system design can serve as a reference for BPKARSS, streamlining and expediting the entire business trip process, enhancing overall efficiency.